Lifetime and 1-Month Prevalence of Mental Disorders in Hebei Province, China: A Community-Based Cross-Sectional Study - Sun, Long; Zhang, Yunshu; Cui, Lijun; Li, Jianfeng; Li, Lin; Sun, Xiuli; Liu, Yongqiao; Zhang, Lili; Li, Keqing (Frontiers in Public Health, 2021)
Background: The prevalence of mental disorders is an important topic, which has been reported in different countries in the world. In China, some studies were also conducted to get the prevalence of mental disorders at the national level and in some metropolitan cities. However, the prevalence of mental disorders in Chinese underdeveloped provinces has not been reported internationally in recent decades. Due to the discrepancy in the social-economic development of different Chinese provinces, we also have reasons to believe the different prevalence of mental disorders between underdeveloped provinces and other provinces. Method: A community-based cross-sectional study was conducted among community residents aged 18 years and older in Hebei province, China. We screened 20,884 community residents in this study, and a Structured Clinical Interview for Diagnostic and Statistical Manual (DSM-IV) Axis I disorders was used to make the diagnoses of mental disorders. Results: The weighted lifetime prevalence of mental disorders was 15.87% (95% CI 15.38–16.38%), and the 1-month prevalence was 10.79% (95% CI 10.37–11.22%). Anxiety disorder ranked first in the classification of mental disorders for both lifetime (6.56%) and 1-month prevalence (6.25%). The weighted lifetime and 1-month region–gender–age-specific prevalence of mental disorders was also analyzed in this study. Conclusions: Mental disorders have been an important issue in Chinese economically underdeveloped regions, and the prevalence was at a high level compared with the results in the 2000s. There are several serious challenges in the work of Chinese mental disorders, which should be paid more attention to.